Extracellular vesicles (EVs) in seminal plasma of buffalo bulls possess spermatozoa specific fertility associated proteins and enzymes - Rakesh Kumar; Mir Ahmad; Bala Subramaniam; Ankit Pal; Aditya Patel; Shiva Shiva; Vitika Chauhan; Seema Karanwal; Mukesh Bhakat; Tirtha K. Datta (Revista Científica)
Buffaloes are the backbone of the Indian dairy and live-stock industry. They contribute nearly 53% of milk and 30% of meat production in India. Bull fertility is vital to productivity, sustainability, and efficient buffalo farming. The current study aims to assess the extracellular vesicles (EVs) based fertility marker in the seminal plasma of buffalo bulls. The seminal plasma of buffalo bulls of contrasting fertility was utilized to purify EVs by size exclusion chromatography (SEC). Diffraction light scattering (DLS), nano-tracking assay (NTA), and Western blotting were used to confirm seminal plasma EVs. A pure population of EVs was obtained in 7-12 SEC fractions with an average EV size of 161nm. The NTA analysis provides a quantitative abundance of EVs, and the EVs population was 1.5x109 to 2.9x1011 EVs/ml in seminal plasma. Utilizing the Western blotting approach, the abundance of SPAM-1 protein in EVs was significantly high in high fertile (HF) bulls as compared to low fertile (LF) group (p <0.05). However, disintegrin and metalloproteinase domain-containing protein 7 (ADAM-7) and acrosomal protein SP-10 were not significantly different in seminal EVs of HF and LF bulls. Similarly, the abundance of Gelectin-3 and aldose reductase (AR) was comparatively higher in HF groups, although it was insignificant. The fertility factor, CD9 protein, was significantly abundant in the seminal EVs of HF vis a vis LF buffalo bulls, suggesting that CD9 of seminal EVs origin could help assess the fertility status of buffalo bulls. Enzymatic phospholipase A2 (PLA2) activity in HF was higher than in LF seminal EVs, indicating superior PLA2 activity in highly fertile bull semen. Uptake of EV-associated fertility proteins by spermatozoa was assessed. We observed that protein cargo was successfully assimilated with sperm. Finally, LC-MS/MS-based high throughput proteome was performed to identify the differential abundance of protein cargo in seminal EVs of contrasting fertility bulls. We identified the top twenty differently abundant proteins in seminal EVs of HF bulls vis-à-vis LF bulls. The identified proteins were strongly related to sperm functions. Thus, the present study supports that buffalo seminal EVs possess vital fertility-associated proteins and enzymes, which could be important markers for assessing buffalo bull fertility.